Do University Students Have a Good Quality of Sleep?: An Exploratory Study - Dr. Fahmi Hassan Fadhel; prof.dr. Nabil Saleh Sufyan (Taez University, 2023)
Background: Sleep is an important factor in activity and achievement. This study aims to examine the quality of sleep among university students in Yemen and Saudi Arabia.      Methods: An online survey method was used. The sample size was (636) (46.23% female N=294, 36.64% N= 233 Yemeni students and 63.36% N=403 Saudi students). Participants responded to Arabic version of the Pittsburgh Sleep Quality Index (PSQI) and the Sleep Difficulties Questionnaire (SDQ).      Results: The prevalence of poor sleep quality among university students was (25.63%) and sleep difficulties was (25%). A total of 23.60% of Yemeni students had poor sleep quality and 27.90% had sleep difficulties.  While, 26.79% of Saudi students had poor sleep quality and 23.32% had sleep difficulties.  There were no significant differences between students of two countries in sleep quality or sleep difficulties. Quality of Sleep and Sleep difficulties were significantly correlated with academic performance in the overall sample and in the group of Saudi students.      Conclusions: The prevalence of poor sleep quality and sleep difficulties is high among university students, which may negatively affect their academic performance. There is an urgent need for psychological intervention, as well as a need for more research in this field.